Survei Pengelolaan Klub Sepak Bola SSB GP PLANDI Jombang yang Berdampak Pada Prestasi Atlet - Mohammad Ilham Maulana; Wing Prasetya Kurniawan; Dhedy Yuliawan (Journal of Physical Activity and Sports (JPAS), 2023)
The background of this research is the results of the author's observations of the activities of a soccer club in Plandi Village called SSB GP Plandi. This club's training seems the same as other clubs, but this club often wins matches inside and outside the city. Therefore the author wants to examine what management or management is carried out by the coaches and administrators of the SSB GP Plandi club in maintaining the achievements of their athletes. This research approach uses a survey approach with a type of qualitative research by seeking information from related parties in the cluster such as coaches, administrators, and athletes. Data is collected by the type of data from the results of interviews, documentation, and observation. In the results of the study, the coach stated that with advanced planning and short, medium, and long-term management management was able to guide children to improve their soccer skills. Trainers always instill discipline and appropriate training methods. This is expected to maximize the potential of each individual. Training and evaluation program, SSB GP Plandi's coach provides an intensive training program which is 4 times a week with some core training such as passing, ball control, heading, free kicks, and penalty kicks. In the facilities and infrastructure section, the trainer stated that the facilities and infrastructure at SSB PG Plandi were still good and complete for regular training, and the trainer was more pleased because there were already lights from the provision of facilities so they could be used at night. Based on the research conclusions, the authors stated (1) the training was very intensive, based on the acknowledgments of coaches, athletes, and administrators said that the training was carried out intensively four times a week, namely Monday, Wednesday, Friday, and Saturday which focused on passing, control, heading, free kicks and penalty kicks and other physical exercises. (2) developing planning for advanced training and short, medium, and long-term management in management that is able to guide children to improve their abilities and instilling a disciplined attitude supported by appropriate training is expected to maximize the potential in each individual.